Mechanisms of Textual Cohesion in Conversations from Facebook - Perez Retana, David (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2017)
This article presents the results of the research “Mechanisms of Textual Cohesion in Conversations on Facebook”, prepared to qualify for the master degree in Linguistics from the University of Costa Rica. The objective is to analyze the mechanisms of textual cohesion used by Facebook users. The analysis is based on the theoretical contributions of textual linguistics of Beaugrande and Dressler, concerning textuality. The study shows the existence of textual mechanisms specialized in linking different interventions into one conversation, while others mechanism are oriented to linking textual elements in the same intervention. Additionally, the frequency of use of these mechanisms is detailed (connection, reference, ellipsis and lexical cohesion).